Anti-inflammatory effect of sea buckthorn in an HCl-induced cystitis rat model - Hyun Suk Yoon; Juyeon Yu; Shinhoon Kang; Hana Yoon (Investigative and Clinical Urology)
"Purpose: Although the mechanism underlying interstitial cystitis/bladder pain syndrome (IC/BPS) remains unclear, oxidative stress is suggested to be implicated in IC/BPS development. Sea buckthorn (SB; Hippophae rhamnoides L.) contains several compounds with antioxidant properties. In addition, intravesical application of hydrochloric acid (HCl) in rats induces histological changes similar to those observed in humans with IC. Therefore, the aim of this study was to evaluate the anti-inflammatory effects of SB in an HCl-induced rat cystitis model. Materials and Methods: Twenty 8-week-old female Sprague–Dawley rats were instilled with HCl in their bladders to create an IC/BPS model. The model rats were divided into three groups and orally administrated distilled water (control, n=4), concentrated SB (n=8), or pentosan polysulfate (PPS, n=8) daily. Pathologic inflammation grade (H&E staining), number of mast cells per square millimeter (toluidine blue staining), fibrotic changes (Masson’s trichrome staining), and apoptosis (terminal deoxynucleotidyl transferase dUTP nick end labeling staining) of bladder tissue samples were compared among the groups. Results: Compared to the control group, the SB and PPS groups showed reduced edema (5.25±0.96 vs. 2.25±0.46 vs. 2.50±0.54, p=0.004, p=0.005, respectively), number of mast cells (12.5±3.6 vs. 6.8±1.9 vs. 6.6±1.8, p=0.010, p=0.002, respectively), ratio of fibrotic submucosal tissue (63.9%±7.0% vs. 43.6%±9.9% vs. 40.5%±5.2%, p<0.001, p<0.001, respectively), and ratio of apoptotic nucleus (40.7%±11.7% vs. 7.7%±6.5% vs. 5.1%±4.9%, p<0.001, p<0.001, respectively). Conclusions: SB exhibited anti-inflammatory effects comparable to those of PPS in the HCl-induced chemical cystitis model."